Analysis of Sakhalin-Ainu lacquerwares by pyrolysis gas chromatography/mass spectrometry. (August 2018) - Idei, Soichiro; Honda, Takayuki; Lu, Rong; Miyakoshi, Tetsuo
Abstract: Six pieces of Sakhalin-Ainu lacquerware were analyzed by pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) to determine the lacquer source. In the direct Py-GC/MS, 3-heptylphenol (P7) and 3-pentadecylphenol (P15) were detected in the mass chromatograms at m / z = 108, and palmitic acid and stearic acid were detected at m / z = 60 in the mass chromatograms of all pieces of Sakhalin-Ainu lacquerware, implying that drying oil was added to sap collected from a Toxicodendron vernicifluum lacquer tree to prepare the lacquer. The energy dispersive X-ray fluorescence results showed that the component ratio of base ground powder was similar to that of Aizu and Joboji lacquerwares, and the Fourier transform infrared spectroscopy results showed that Sakhalin-Ainu lacquerwares used persimmon tannin in the base ground powder like Joboji lacquerwares, suggesting that Sakhalin-Ainu lacquerwares were produced in Joboji, Japan. Based on these results, the production district, history, and culture of the Sakhalin-Ainu lacquerwares are discussed. Graphical abstract: Sakharin-Ainu lacquerware, cross section photo and its layer image structure. Unlabelled Image Highlights: Six valuable ancient Sakharin-Ainu lacquerwares were analyzed. Identification of coating material and additive pigments by Py-GC/MS Identification of lacquerwares production district by comparing the lacquer technology